2018
DOI: 10.1097/dss.0000000000001509
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Ratings of Minimally Invasive Fat Reduction Procedures: Benchmarking Against Traditional Liposuction

Abstract: A large number of patient reviews suggest that minimally invasive fat reduction procedures have high patient satisfaction, although liposuction still had the highest total patient satisfaction score. However, there are significant pitfalls in interpreting patient reviews, as they do not provide important data such as a patient's medical history or physician experience and skill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Indeed, almost all subjects showed substantial improvements in skinfold thickness and corresponding clinically significant improvements in body contour, with only one of 28 patients considered to be a nonresponder. Importantly, the greater improvements in body contouring observed in the skinfold thickness assessment also appeared to enhance patient‐reported outcomes: the patient satisfaction rate (88%) was higher than has been previously observed 7,15 …”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Indeed, almost all subjects showed substantial improvements in skinfold thickness and corresponding clinically significant improvements in body contour, with only one of 28 patients considered to be a nonresponder. Importantly, the greater improvements in body contouring observed in the skinfold thickness assessment also appeared to enhance patient‐reported outcomes: the patient satisfaction rate (88%) was higher than has been previously observed 7,15 …”
Section: Discussionmentioning
confidence: 72%
“…Importantly, the greater improvements in body contouring observed in the skinfold thickness assessment also appeared to enhance patient-reported outcomes: the patient satisfaction rate (88%) was higher than has been previously observed. 7,15 The one patient who did not respond to treatment had received swelling, sensitivity, and pain, which have generally resolved rapidly. 4 We considered these minor and short-lived effects as expected sequelae of the treatment and did not record them as AEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four techniques represent the leading noninvasive modalities available: cryolipolysis, radiofrequency, high‐intensity focused ultrasound, and laser therapy 2,3 . A study assessing subjects' satisfaction with minimally invasive procedures reported in social media found that cryolipolysis had similar rates of satisfaction when compared with liposuction (55% vs 66%) 4 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 A study assessing subjects' satisfaction with minimally invasive procedures reported in social media found that cryolipolysis had similar rates of satisfaction when compared with liposuction (55% vs 66%). 4 Cryolipolysis is a nonsurgical technique for localized fat reduction. Controlled freezing is used to reduce subcutaneous tissue, without skin and adjacent tissue injury, based on the hypothesis that the adipose tissue is highly sensitive to low temperatures.…”
mentioning
confidence: 99%